(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Sturge-Weber syndrome is a congenital, neurocutaneous disorder, with an incidence of 1 in 20,000 - 50,000 births, characterized by a port wine-colored facial and scalp patch, leptomeningeal angiomatosis and glaucoma, caused by a change in the GNAQ gene on chromosome 9 (9q21.2). It has no clear genetic pattern so there is no direct evidence of hereditary predisposition. Early diagnosis is necessary as there may be complications such as glaucoma, vascular stenosis, epilepsy, neurological and neurocognitive impairment. This article aims to describe the case of a rare syndrome, its clinical manifestations and treatment. Case report: 8-year-old male patient with a history of seizures since 7 months of age associated with Sturge Weber syndrome, treated with oxcarbazepine and phenobarbital. At the age of 3 years, during his hospitalization, he presented several tonic-clonic seizures, cardiorespiratory arrest and was started with advanced CPR for two minutes. Brain angioresonance was performed, which reported angiomatosis in left sigmoid sinuses and encephalic magnetic resonance imaging, which reported left temporal parietal occipital cortical atrophy associated with linear and nodular millimetric calcifications. Thanks to current research it is known that the syndrome is produced by a mutation in the GNAQ gene, however, its etiology is not yet proven. The development of this clinical case provides important information on the onset and clinical course of WSS manifested by facial angioma, glaucoma and seizures at an early age.